First Data on WGS-Based Typing and Antimicrobial Resistance of Human Salmonella Enteritidis Isolates in Greece - Michalis Polemis; Theologia Sideroglou; Anthi Chrysostomou; Georgia D. Mandilara (MDPI AG, 2024)
Salmonella enterica subsp. enterica serotype Enteritidis (S. Enteritidis) is one of the major causes of foodborne infections and is responsible for many national and multi-country foodborne outbreaks worldwide. In Greece, human salmonellosis is a mandatory notifiable disease, with laboratory surveillance being on a voluntary basis. This study aims to provide the first insights into the genetic characteristics and antimicrobial resistance profiles of 47 S. Enteritidis human isolates using whole-genome sequencing (WGS) technology. The S. Enteritidis population was mainly resistant to fluoroquinolones due to gyrA point mutations, whereas one isolate presented a multi-resistant plasmid-mediated phenotype. ST11 was the most frequent sequence type, and phylogenetic analysis through the cgMLST and SNP methods revealed considerable genetic diversity. Regarding virulence factors, 8 out of the 24 known SPIs and C63PI were detected. Due to the observed variability between countries, it is of utmost importance to record the circulating S. Enteritidis strains' structure and genomic epidemiology at the national level. WGS is a valuable tool that is revolutionizing our approach to Salmonella by providing a deeper understanding of these pathogens and their impact on human health.